Pengaruh Kualitas Pelayanan, Promosi, dan Suasana Toko dalam Meningkatkan Kepuasan serta Loyalitas Pelanggan: Studi Kasus Momoyo Cabang Balige - Paulus Simorangkir; Trisya Juniastika; Joy Mayadinata; Safrina Manik; Santi Agustina Manalu (ProBisnis : Jurnal Manajemen, 2025)
This study aims to analyze how service quality, promotion, and store atmosphere can affect customer satisfaction and loyalty at Momoyo Balige Branch. The method used involves an explanatory quantitative approach, through a survey conducted on 251 respondents from Del Institute of Technology students. The data from the survey was then analyzed using multivariate regression techniques. The results of the study show that the three independent variables have a positive and significant effect on customer satisfaction and loyalty. Service quality and store atmosphere appear to be the most dominant factors here, while promotion has the least influence, although it is still significant overall. Findings such as these truly emphasize the importance of continuously improving service standards, store comfort, and relevant promotions in order to build customer satisfaction and loyalty in a sustainable manner.